Analysis of Factors Related to Triage Competence with Online Learning Methods to Students at Hafshawaty Genggong University - Moh Husyn Ainul Yaqin; Yulian Wiji Utami; Dina Dewi Sartika Lestari Ismail (Universitas Aisyah Pringsewu, 2022)
During the Covid-19 pandemic, offline learning was shifted to online learning. one of the applications is Zoom Meeting, which is easy to use. The zoom application combines in displaying material in power points learning and feedback communications. One of the challenges in online learning is triage learning such as the Australian triage scale (ATS), ATS itself is a type of triage with five categories. ATS material is a learning achievement that must be mastered by students, but not much research has been done on online learning methods with ATS material. The method used in this study is an observational analytic method using a cross-sectional approach, the researcher takes data from several variables that exist at the same time. There are three factor namely technological factors, student characteristics factors and teacher characteristics. Results: The results of the study several influential factors were obtained namely, technology factors with a p-value of 0.013, student characteristics factors with a p-value of 0.029, and student characteristics factors of 0.003. Teacher characteristics factor with a p-value of 0.029. The three factors have a relationship with students' triage competence with the online method. Conclusion: The three factors have a significant relationship, but there is no most significant factor yet. Abstrak: Di masa pandemi Covid-19, pembelajaran offline digeser menjadi pembelajaran online. salah satu aplikasinya adalah Zoom Meeting yang mudah digunakan. Aplikasi zoom menggabungkan dalam menampilkan materi dalam pembelajaran power point dan komunikasi umpan balik. Salah satu tantangan dalam pembelajaran online adalah pembelajaran triase seperti Australian triage scale (ATS), ATS sendiri merupakan jenis triase dengan lima kategori. Materi ATS merupakan prestasi belajar yang harus dikuasai oleh siswa, namun belum banyak penelitian yang dilakukan terhadap metode pembelajaran online dengan materi ATS. Metode yang digunakan dalam penelitian ini adalah metode observasional analitik dengan menggunakan pendekatan cross sectional, peneliti mengambil data dari beberapa variabel yang ada dalam waktu yang bersamaan. Ada tiga faktor yaitu faktor teknologi, faktor karakteristik siswa dan karakteristik guru. Hasil: Hasil penelitian diperoleh beberapa faktor yang berpengaruh yaitu, faktor teknologi dengan nilai p 0,013, faktor karakteristik siswa dengan nilai p 0,029, faktor karakteristik siswa 0,003. Faktor karakteristik guru dengan p-value 0,029. Ketiga faktor tersebut memiliki hubungan dengan kompetensi triase siswa dengan metode online. Kesimpulan: Ketiga faktor tersebut memiliki hubungan yang signifikan, namun belum ada faktor yang paling signifikan.